Islamic Perspectives on Architectural Art: A Comprehensive Review (Jagannath University Journal of Arts, 2026)
Islamic architectural art is a profound manifestation of cultural, spiritual and aesthetic values deeply rooted in Islamic Principles. This comprehensive study explores the philosophical, historical and artistic dimensions of Islamic architecture, emphasizing its evolution, key characteristics and various socio-religious influences. The 21st century has witnessed the construction of colossal architectural marvels-gleaming skyscrapers and futuristic complexes-designed with state-of-the-art facilities to meet modern demands. This paper explores its definition according to Islamic principles and the Islamic perspective on its design, purpose and ethical considerations. Drawing from primary Islamic sources, the study examines how Islamic teachings, functionality, and spirituality intersect. Key themes include the relationship between the Islamic worldview and architectural expressions, Islam’s directives on art and construction and the balance between beauty and religious value. The discussion is presented in a clear and engaging manner to enhance readers’ understanding of Islamic architectural philosophy.Jagannath University Journal of Arts, v-15, i-2, 2025:p128-136